Pengaruh Dimensi Kualitas Layanan Jasa Terhadap Tingkat Kepuasan Nasabah Koperasi (Studi Kasus pada Koperasi Simpan Pinjam Lumbung Merta Sari, Badung) - Priskila, Rissa; Pramudana, Km. Agus Satria (E-Jurnal Manajemen; Vol 2 No 7 (2013), 2013)
This research purpose is to determine the effect of service quality dimensions on customer satisfaction in saving and credit cooperative Lumbung Merta Sari, Badung. The sampling techniques that used in this research is purposive sampling. Techniques of analysis data used in this research is multiple linear regression. This analysis is used to determine the influence magnitude of service quality dimensions on customer satisfaction. The obtained results showed that the dimensions of service quality simultaneously and partially affect the customer satisfaction in saving and credit cooperative Lumbung Merta Sari, Badung. Keywords: Service Quality, Customer Satisfaction